Colorectal cancer chemoprevention: the potential of a selective approach. Issue 10 (October 2010) - Ben-Amotz, Oded; Arber, Nadir; Kraus, Sarah
Evaluation of: Zhang L, Ren X, Alt E et al. Chemoprevention of colorectal cancer by targeting APC-deficient cells for apoptosis. Nature 464(7291), 1058–1061 (2010). Colorectal cancer (CRC) is a leading cause of cancer death, and therefore demands special attention. Novel recent approaches for the chemoprevention of CRC focus on selective targeting of key pathways. We review the study by Zhang and colleagues, evaluating a selective approach targeting APC -deficient premalignant cells using retinoid-based therapy and TNF-related apoptosis-inducing ligand (TRAIL). This study demonstrates that induction of TRAIL-mediated death signaling contributes to the chemopreventive value of all- trans -retinyl acetate (RAc) by sensitizing premalignant adenoma cells for apoptosis without affecting normal cells. We discuss these important findings, raise few points that deserve consideration, and may further contribute to the development of RAc-based combination therapies with improved efficacy. The authors clearly demonstrate a synergistic interaction between TRAIL, RAc and APC, which leads to the specific cell death of premalignant target cells. The study adds to the growing body of literature related to CRC chemoprevention, and provides solid data supporting a potentially selective approach for preventing CRC using RAc and TRAIL.